IBRAHIM B. ADHAM: THE IMAGE OF THE “HOLY RULER” IN THE ISLAMIC TRADITION - Alikberov, Alikber Kalabekovic (History, Archeology and Ethnography of the Caucasus, 2018)
Abu Iskhaq Ibrahim B. Adham al-Balkhi is well known in Muslim Historiography as the famous mystic and ascetic who lived in Balkh region in the 8th century. The early sources portray him as a ruler’s son who gave up riches of the worldly life and devoted himself to the service of God. The most important of these sources are: “Tabaqat as-sufiya” by Abu ‘Abd ar-Rahman as-Sulami, “Hilyat al-awliya” by Abu Nu‘aym al-Isfahani, “Tabaqat as-sufiya” by Abu ‘Abdallah Ansari, “Ar-Risala fi-‘ilm at-tasawwuf” by Abu ’l-Qasim al-Qushayri, “Salwat al-‘arifin” by Abu Khalaf at-Tabari and “Rayhan al-haqa’iq” by Abu Bakr Muhammad al-Darbandi. It is especially important to trace the spiritual continuity of the early Sufi tradition: ad-Darbandi received the written permission ( al-ijaza ) from Abu Khalaf at-Tabari, who was a disciple of Abu’l-Qasim al-Qushayri. The later sources (Farid ad-Din ‘Attar’s “Tadhkirat al-awliya”, Maulana Rumi’s “Masnawi”, etc.) show Ibrahim B. Adham as a ruler who becomes a saint. The transformation of the image of the saint, who came from the dynasty of the rulers of Balkh, can be clearly traced in the miniatures of the Mughal School, resonating with the images of the “holy rulers” of the Mughal dynasty. The image of Ibrahim B. Adham infiltrated to India and Indonesia, where it acquired additional mythological features.
Keywords: early Ṣufi tradition; Ibrahim B. Adham; al-Qushayri; Abu Bakr al-Darbandi; Arabic manuscripts; Indian miniatures; Mughal School